THE ANALYSIS OF THE COMMUNITY-ACQUIRED PNEUMONIA COURSE IN CHILDREN OF ROSTOV-ON-DON - O. E. Semernik; A. A. Lebedenko; E. B. Tyurina; S. Kh. Luspikayan (Сеченовский вестник, 2019)
Objective - to study the clinical features of community - acquired pneumonia in children of Rostov - on - Don. Materials and methods. To achieve this goal, 261 cases of children aged 1 month to 17 years who were admitted to the hospital with suspected community - acquired pneumonia were analyzed. All patients underwent a thorough analysis of anamnestic data, the results of clinical examination of patients, laboratory diagnostics, and X-ray chest examination. Results. The study showed that the highest incidence of community - acquired pneumonia was observed in children aged 8 to 12 years. Boys get sick more often than girls. More often, pulmonary parenchyma lesions were observed, localized on the right side of 66%, while the bilateral process was registered only in 10%. According to the morphological form, segmental - 42% and focal - 34% lesions were most often registered, polysegmental were 17%, and equity - 1%. The results of X- ray examination of patients allowed to conﬁrm the diagnosis of community - acquired pneumonia in most patients. Conclusion. The most common clinical and morphological form of pneumonia in children remains focal and segmental forms with a high prevalence of right - sided pneumonia.